Inhibitor to Factor VIII in Mild Haemophilia - Kesteven, P J; Holland, L J; Lawrie, A S; Savidge, G F (Thrombosis and Haemostasis, 1984)
Factor VIII inhibitors in mild haemophilia are uncommon and the management of such patients is controversial. The development of a persistently high responding F VIII inhibitor in a mild haemophiliac is reported and the behaviour of the inhibitor discussed in the context of the various therapeutic regimes employed for symptomatic management. When inhibitor titres were low, endogenous F VIII stimulation, by DDAVP, was less immunogenic than the administration of exogenous F VIII concentrates. This inhibitor displayed characteristics of an autoantibody, and was characterised as an immunoglobulin of IgG subtype.
Keywords: F VIII inhibitors; Activated prothrombin complex concentrates; Porcine F VIII; DDAVP